IMPLEMENTASI KEBIJAKAN E-TILANG BAGI SASARAN MASYARAKAT - Prima A., Teddy; Fauzia, Laily Farah; Ghanksar Y.L., Vincentius Yohannes; Syahfrudin, Muhammad Arief; FRisandia, MicselinSifa (UNIVERSITAS SERAMBI MEKKAH, 2024)
This research aims to provide an understanding related to law enforcement through the E-Ticket system policy, because currently there are still many people who still violate the rules in driving. Therefore, research is needed that aims to provide direction in terms of the E-Tilang process, the current application of E-Tilang does go through several things that must be considered. E-tickets carried out at this time have a deterrent effect on people who violate, as for the deterrent effect experienced by the community, namely the fines given to violators. So that with the fines given some people become deterrent, but most people are still disobedient in driving on the highway even though E-Tilang has been carried out. Therefore, with the events that often occur in the community regarding E-Tilang, socialization is needed, to provide understanding and understanding to the community that when driving several things are needed that must be considered in order to maintain safety.